Learning About a New Technology: Pineapple in Ghana - Timothy G. Conley; Christopher R. Udry (Yale University, Economic Growth Center, 2000)
This paper investigates the role of social learning in the diffusion of a new agricultural technology in Ghana. We use unique data on farmers communication patterns to define each individuals information neighborhood, the set of others from whom he might learn. Our empirical strategy is to test whether farmers adjust their inputs to align with those of their information neighbors who were surprisingly successful in previous periods. We present evidence that farmers adopt surprisingly successful neighbors practices, conditional on many potentially confounding factors including common growing conditions, credit arrangements, clan membership, and religion. The relationship of these input adjustments to experience further supports their interpretation as resulting from social learning. In addition, we apply our methods to input choices for another crop with known technology and they correctly indicate an absence of social learning effects.
Keywords: O31; O12; O13; 330; Social Learning; Technology; Innovation; Technischer Fortschritt; Agrartechnik; Innovationsdiffusion; Lernprozess; Tropische Frucht; Ghana